MATHEMATICS TEACHERS RESPONSES TO STUDENTS MISCONCEPTIONS IN ALGEBRA (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
The study investigated the responses of teachers of mathematics to students misconceptions in algebra. Qualitative approach to the analysis of the data was employed. Eighty seven teachers took part in the study, and four questionnaires were designed to explore the responses of the teachers. The focus was on variables, algebraic fractions, equations and word problems. The study revealed that some of the teachers were successful in understanding students thinking with regard to the algebraic concepts studied. The study also indicated that most teachers ask instructional questions instead of investigative questions. Most teachers were incapable of asking questions which would reveal students source or cause of misconception. Another important finding was that some of the teachers had difficulties in understanding the problems, hence could not figure out the students  misconceptions or errors in the hypothetical solutions given in the questionnaires. The teachers pedagogical content knowledge was generally inadequate.